Geographic Differences in Availability and Access to Care Services for Asthma and COPD: Case Study of Vancouver Coastal Health, British Columbia - Amelia Choy; Erin M. Shellington; Aneisha Collins-Fairclough; Nardia Strydom; Chris Carlsten (Canadian Respiratory Journal)
Conclusion: Our findings suggest rural VCH communities have lower access to asthma and COPD care services and the limited urban care services were insufficient to make up for this difference. Past asthma and COPD QI initiatives have not apparently translated to care service improvements in rural regions. Future QI initiatives should focus on overcoming barriers to conducting and participating in QI to improve urban and rural regions’ access to asthma and COPD care services.